2017
DOI: 10.1155/2017/6504518
|View full text |Cite|
|
Sign up to set email alerts
|

The Utility of Ovotransferrin and Ovotransferrin‐Derived Peptides as Possible Candidates in the Clinical Treatment of Cardiovascular Diseases

Abstract: Several of the most prevalent etiological factors which contribute towards global death rates are associated with cardiovascular diseases (CVDs), which include a range of conditions such as angina, rheumatic heart disease, and venous thrombosis. Extensive research has been conducted into the role played by oxidative stress and inflammation in the functional transformations associated with the progression of CVDs, while the research findings from these investigations have been both fruitful and informative. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…In this study, the administration of IQW to AS model mice was found to delay progression of the disease, reduce the arthritic grade of intervertebral joints and reduce the concentrations of IL‐6, IL‐1β and TNF‐α. The expression of cytokine‐induced inflammatory protein in the vascular endothelium can be successfully downregulated by administration of IRW (Ile‐Arg‐Trp) and IQW derived from the egg‐white protein ovotransferrin (Majumder and Wu ; Chen et al ). These anti‐inflammatory effects are exerted at least partly by alteration of the NF‐κB pathway (Kaustav et al ) and have sometimes been accompanied by additional beneficial antioxidant effects (Huang et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the administration of IQW to AS model mice was found to delay progression of the disease, reduce the arthritic grade of intervertebral joints and reduce the concentrations of IL‐6, IL‐1β and TNF‐α. The expression of cytokine‐induced inflammatory protein in the vascular endothelium can be successfully downregulated by administration of IRW (Ile‐Arg‐Trp) and IQW derived from the egg‐white protein ovotransferrin (Majumder and Wu ; Chen et al ). These anti‐inflammatory effects are exerted at least partly by alteration of the NF‐κB pathway (Kaustav et al ) and have sometimes been accompanied by additional beneficial antioxidant effects (Huang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring peptides and proteins have shown significant promise for the prevention, management or treatment of AS, largely due to their versatility as starting materials for the formulation of novel compounds with advantageous biological effects (Orekhov ). In particular, cytokine‐induced inflammatory protein expression is effectively downregulated by Ile‐Gln‐Trp (IQW, obtained from egg white), at least partly via adjustment of the NF‐κB pathway (Kaustav et al ; Chen et al ). Moreover the positive results of such anti‐inflammatory functions are often enhanced by concomitant antioxidant effects (Huang et al ; Liu et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also associated changes in dietary habits (particularly the adoption of a HFD) with gut microbiota dysbiosis, which suggests clear consequences in terms of metabolic disorders (Chen et al ; Yin et al ). Along with the above‐mentioned positive effects of dietary quercetin on metabolic and immune responses, this study also revealed the beneficial impacts of quercetin on dysbiosis in mice fed a HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing interest has been directed towards the search for natural substances that may assist with CVD treatment. Health-promoting adjustments in lifestyle and dietary habits, including cognitive-behavioural therapy, physical exercise and a personalized diet, represent the most cost-effective forms of CVD management (Tangney and Rasmussen 2013;Chen et al 2017;Ding et al 2018). Notably, several investigations have also identified the dietary intake of polyphenols as a potential option for CVD management (Tangney and Rasmussen 2013;Ding et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the successful inhibition of cytokine-induced inflammatory protein expression in vascular endothelium, at least in part via the modulation of the NF-B pathway, in the presence of two novel peptides, namely IRW and IQW, which are derived from the egg white protein ovotransferrin [13][14][15]. In addition to this anti-inflammatory effect, the observed advantages of these peptides have included antioxidant effects [16].…”
Section: Introductionmentioning
confidence: 99%